Comparison of a web-based package with tutor-based methods of teaching respiratory medicine: subjective and objective evaluations. - Smith,SF; Roberts,NJ; Partridge,MR (BMC Med Educ, 2007)
BACKGROUND: Respiratory disease is a major cause of morbidity and mortality not only in the United Kingdom, but globally. A good understanding of respiratory disease and its treatment is essential for all medical graduates. As a result of changes in clinical practice, patients with some common respiratory illnesses are less often admitted to hospital, restricting the experience available to undergraduate students. Combined with a potential shortage of clinical teachers, this means that new methods of teaching need to be developed and appraised. The aim of this study was to establish whether a web-based package on the diagnosis of respiratory disease would be as effective and as acceptable to final year medical students as tutor-led methods of teaching the same material. METHODS: 137 out of 315 final year undergraduate students in a single medical school volunteered to take part. Each received up to two hours of tutor-lead interactive, tutor-lead didactic or electronic, Web-based teaching on the accurate diagnosis and management of respiratory disease. Post teaching performance was assessed by multiple true/false questions and data interpretation exercises, whilst students' teaching preferences were assessed by questionnaire. RESULTS: Despite a high knowledge baseline before the study, there was a small, but statistically significant increase in knowledge score after all forms of teaching. Similarly, data interpretation skills improved in all groups, irrespective of teaching format, Although paradoxically most students expressed a preference for interactive tutor-lead teaching, spirometry interpretation in those receiving web-based teaching improved significantly more [p = 0.041] than in those in the interactive group. CONCLUSION: Web-based teaching is at least as good as other teaching formats, but we need to overcome students' reluctance to engage with this teaching method.